2018
DOI: 10.1159/000495572
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Molecular Biomarkers Associated with Early Neurological Deterioration Following Acute Stroke

Abstract: Background: Early neurological deterioration (END) following acute stroke is associated with poorer long-term outcomes. Identification of patients at risk could assist early monitoring and treatment decisions. This review summarised the evidence describing non-radiological biomarkers for END. Summary: Electronic searches from January 1990 to March 2017 identified studies reporting a blood/cerebrospinal fluid (CSF)/urine biomarker measurement within 24 h of acute stroke and at least 2 serial assessments of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 50 publications
4
28
0
Order By: Relevance
“…To prove the association of BPV and END, we adopted a definition of END as a ≥1‐point increase in NIHSS score during the first 72 hours after admission. And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To prove the association of BPV and END, we adopted a definition of END as a ≥1‐point increase in NIHSS score during the first 72 hours after admission. And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study .…”
Section: Discussionsupporting
confidence: 92%
“…And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies. [4][5][6][7][8][9][10] And also, our findings were similar to that in the Chungs' study. 16 Both studies suggested that the acute in-hospital BPV was strongly associated with the risk of having a END.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The influence of hs-CRP on ischemic stroke has been well established, and hs-CRP has been reported as a predictor of disease severity, prognosis and mortality in patients with ischemic stroke [19, 29]. Furthermore, high plasma hs-CRP levels are associated with clinical complications following acute ischemic stroke [18, 30] PMD, which may result in severe morbidity, commonly occurs in patients with PAI during the acute stage. This is the first study to explore the relationship between hs-CRP and PMD in patients with penetrating artery ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%